Design and Build a Saghai Ball Thrower at the 2019 Indonesian Abu Robot Contest - Setiyabudi, Tri; Aji, Wahyu Sapto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
Abu Robocon 2019 will be held in the country of Mongolia with the competition theme